Ion migration and defect effect of electrode materials in multivalent-ion batteries - Liu, Zhexuan; Qin, Liping; Cao, Xinxin; Zhou, Jiang; Pan, Anqiang; Fang, Guozhao; Wang, Shuangyin; Liang, Shuquan (Progress in materials science, 2022)
We have highlighted the fundamental principles of ion diffusion and discussed the factors that affect the ion diffusion. We also focus on how characteristic parameters of defect engineering cause changes in multivalent-ion diffusion behavior and offer the insightful understanding of defect effects on multivalent-ion diffusion. [Display omitted] The rechargeable multivalent-ion batteries (MVIBs) that transfer Zn2+, Mg2+, Al3+, Ca2+ etc. as charge carriers, have become a research hotspot and been emerging as attractive candidates for grid energy storage in terms of cost, volumetric energy density and safety. But there is still a long way from their maturity due to the challenges related to the limited multivalent-ion diffusion kinetic. Unfortunately, the insightful understanding in this aspect is still at an early stage. In this review, considering the critical role of defect chemistry, we have highlighted the fundamental scientific understanding of its relationship with multivalent-ion migration in electrode materials of MVIBs. We first remarked on the basic principles of ion diffusion, from which we further discussed the key factors affecting ion migration and pointed out the critical issues of multivalent-ion diffusion. More importantly, how characteristic parameters of defect engineering cause changes in multivalent-ion diffusion behavior has been expounded in the areas of ion diffusion path and intrinsic structural parameters. The application of defective electrodes in MVIBs with advanced functions was also discussed. Finally, the future perspectives for important areas of defect chemistry for multivalent-ion migration were presented.